Regulation of Leishmania populations within the host. II. genetic control of acute susceptibility of mice to Leishmania donovani infection. - Bradley, D J (1977)
The acute growth rates of Leishmania donovani populations in twenty-five inbred mouse strains fall into two distinct groups: the susceptible (S) and the resistant (R). Hybrids within either category resemble their parents in susceptibility. Hybrids between categories are moderately resistant. Back-crossing of F1 hybrids to R and S parents, and interbreeding the F1 generation, give susceptibility ratios consistent with single gene control of acute susceptibility to visceral leishmaniasis. The distribution of this character among inbred mouse strains does not correspond to any well-studied gene nor does it appear to be linked to the H2 histocompatibility locus.